DEVELOPMENT OF AN INVENTORY MODEL FOR PHARMACEUTICALS CONSIDERING SHELF LIFE, JOINT REPLENISHMENT, SUBSTITUTE PRODUCTS, MINIMUM ORDER QUANTITY, QUANTITY DISCOUNTS, AND TRANSPORT CAPACITY CONSTRAINTS - Dianty Firas, Shafira
Medicines are an essential, irreplaceable component of healthcare services, making their availability critical. This research identifies several key issues, including overstocking leading to expired drugs, understocking reducing service levels, and challenges in determining optimal order lot sizes. These challenges encompass minimum order quantity, quantity discounts, and transport capacity considerations that have not been comprehensively addressed. This study aims to minimize total inventory costs by addressing these issues. Two reference models are used in this research. The primary reference model is a pharmaceutical inventory model considering shelf life, joint replenishment, and product substitution developed by Siregar (2020). Unaddressed aspects in Siregar's model are supplemented by Liu et al. (2023), which considers quantity discounts, minimum order quantity, and transport capacity. The proposed model aims to comprehensively resolve pharmaceutical inventory problems by addressing fixed shelf life, joint replenishment, product substitution, and logistics constraints. It focuses on two types of medicines with similar or identical active ingredients that are substitutable. The model is designed with two scenarios to determine the role of the medicines: Scenario 1, where Medicine 1 is the main drug and Medicine 2 is the substitute, and Scenario 2, where their roles are reversed. Each scenario has two cases to determine the presence of expired drugs. Case 1 occurs if stock runs out due to demand, leading to no expired drugs, while Case 2 occurs if stock runs out due to shelf life, resulting in expired drugs. For Case 2, two treatments are applied: maintaining the initial solution and adjusting the solution. The total costs of both treatments are calculated and evaluated to select the lowest total inventory cost. Each case has five conditions to determine the purchase price based on quantity discounts: No Discount, Discount 1 (5%), Discount 2 (10%), Discount 3 (15%), and Discount 4 (20%). Based on calculations for 30 groups of medicines, the proposed model shows that the inventory policy for 28 groups can be applied without adjustment, while 2 groups require adjustment. Of these, 7 groups are optimized under Scenario 1 Case